Children's shyness and physiological arousal to a peer's social stress - Poole, Kristie L.; Sosa‐Hernandez, Linda; Green, Emma S.; Wilson, McLennon; Labahn, Claudia; Henderson, Heather A. (Developmental psychobiology, 2023)
Previous work has shown that children's shyness is related to personal anxiety during social stress, but we know little about how shyness is related to anxiety during a peer's social stress. Children (Mage = 10.22 years, SD = 0.81, N = 62) were paired with an unfamiliar peer and engaged in a speech task while electrocardiography was recorded. We modeled changes in children's heart rate, a physiological correlate of anxiety, while they observed their peer prepare and deliver a speech. Results revealed that the observing child's shyness related to increases in their heart rate during their peer's preparation period, but modulation of this arousal was sensitive to the presenting peer's anxious behavior while delivering their speech. Specifically, if the presenting child displayed high levels of anxious behavior, the observing child's shyness was related to further increases in heart rate, but if the presenting child displayed low levels of anxious behavior, the observing child's shyness was related to decreases in heart rate from the preparation period. Shy children may experience physiological arousal to a peer's social stress but can regulate this arousal based on social cues from the peer, which may be due to heightened social threat detection and/or empathic anxiety.